Giant African snail meat as dietary animal protein source for common carp (Cyprinus carpio var. communis Linn.) - Suresh, V R (Indian Journal of Fisheries, 2011)
A laboratory growth trial was conducted to evaluate the suitability of the meat of African snail, Achatina fulica, as dietary protein source for common carp, Cyprinus carpio. Four diets were formulated with varying levels of snail meatand fish meal as animal protein source along with mustard oil cake and a conventional diet containing only mustard oil cake as principal protein source. The diet with fish meal and mustard oil cake produced 345.9% weight gain, followed by the diet in which 25% of the fish meal was substituted with snailmeat (337.5%). Complete substitution of fish meal with snail meat resulted in higher feed conversion and 52.4% higher weight gain over conventional feed. Inclusion of snail meat improved the protein efficiency ratio and proteindigestibility. Meat of African snail could be a cheap and effective protein source in carp supplementary feeds.